2010
DOI: 10.1111/j.1469-8986.2009.00955.x
|View full text |Cite
|
Sign up to set email alerts
|

On the role of conflict and control in social cognition: Event-related brain potential investigations

Abstract: Numerous social-cognitive models posit that social behavior largely is driven by links between constructs in long-term memory that automatically become activated when relevant stimuli are encountered. Various response biases have been understood in terms of the influence of such ''implicit'' processes on behavior. This article reviews event-related potential (ERP) studies investigating the role played by cognitive control and conflict resolution processes in social-cognitive phenomena typically deemed automati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 122 publications
(253 reference statements)
1
31
0
Order By: Relevance
“…Larger frontal (topographical) and dACC (source) LSW amplitude during rejection compared to neutral scenes suggests sustained processing of rejection following voluntary orientation because of deeper semantic processing, in terms of resolving semantic conflict (Bartholow, 2010;Herbert, Herbert, Ethofer, & Pauli, 2011) and preference for motivationally salient scenes (Foti et al, 2009;Franz, Schaefer, Schneider, Sitte, & Bachor, 2004). The LSW may also respond to minimizing social pain, because larger medial frontal LSW amplitude during exclusion from a ball-tossing game was associated with lower ostracism-related distress (Crowley et al, 2010).…”
Section: Schizotypy and Rejection Sensitivity 20mentioning
confidence: 99%
See 2 more Smart Citations
“…Larger frontal (topographical) and dACC (source) LSW amplitude during rejection compared to neutral scenes suggests sustained processing of rejection following voluntary orientation because of deeper semantic processing, in terms of resolving semantic conflict (Bartholow, 2010;Herbert, Herbert, Ethofer, & Pauli, 2011) and preference for motivationally salient scenes (Foti et al, 2009;Franz, Schaefer, Schneider, Sitte, & Bachor, 2004). The LSW may also respond to minimizing social pain, because larger medial frontal LSW amplitude during exclusion from a ball-tossing game was associated with lower ostracism-related distress (Crowley et al, 2010).…”
Section: Schizotypy and Rejection Sensitivity 20mentioning
confidence: 99%
“…The EEG task employed affective priming, because affective primes lead to 'activation spreading' of a semantic context to a target stimulus and anticipation of the prime (Bartholow, 2010;Hietanen & Astikainen, 2013;Lu et al, 2011). Rejection is a complex emotion (Çelik, Lammers, van Beest, Bekker, & Vonk, 2013;Power, 2005) requiring awareness of the circumstances that caused the emotion and therefore higher-order cognitive evaluation (JohnsonLaird & Oatley, Jun 1989).…”
Section: Social Interactions Pictures Taskmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that modulation of the N400 was observed for association and association + semantic word pairs but not for those that only shared a semantic relationship. NSW is another well-known component of ERP broadly distributed over the scalp, which reflects a cognitive conflict or the cognitive control of the conflict, such as the conflict elicited in incongruent Stroop trials (Bartholow, 2010;Curtin & Fairchild, 2003;West & Alain, 1999), or which reflects the difficulty of conceptual operations, such as the semantic processing (Silva-Pereyra, Rivera-Gaxiola, & Kuhl, 2005), complex mnemonic memorization activity (Cansino, Ruiz, & López-Alonso, 1999), and memory search (Kramer, Schneider, Fisk, & Donchin, 1986;Okita, Wijers, Mulder, & Mulder, 1985). The topography of NSWs varies across tasks; Okita et al (1985) found that NSWs with a duration of 400-700 ms were maximal over the centro-posterior scalp in memory scanning tasks, while Kramer et al (1986) revealed that NSWs with a duration of 500-1200 ms were maximal over the frontal scalp.…”
Section: Introductionmentioning
confidence: 99%
“…The P3 is sensitive to individual difference variables (Bartholow, 2010;Polich, 2007), including video game experience (Engelhardt, Bartholow, Kerr, & Bushman, 2011;Bartholow et al, 2006).…”
Section: Chapter 3 Studymentioning
confidence: 99%